Detection of POLE Subtypes in High-Grade Endometrioid Carcinoma by BaseScope-ISH Assay - Yu, Shuangni; Shao, Huilin; Ban, Xinchao; Zhang, Hongkai; You, Yan; Zhou, Na; Mao, Xinxin; Zhao, He; Chen, Jie; Lu, Zhaohui (Frontiers in Oncology, 2019)
OBJECTIVE: The identification of DNA polymerase epsilon (POLE) mutation subtypes in endometrial cancer is critical for molecular classification. The mutation of the POLE gene could only be detected by sequencing until now. We propose to validate and develop the feasibility of using BaseScope, an in situ hybridization (ISH) assay, for the detection of POLE mutations in high-grade endometrioid carcinomas (EC). METHODS: Among 51 paraffin-embedded samples of high-grade EC, BaseScope-ISH assays were used to detect the RNA mutation status of the POLE gene, mainly focusing on two hotspot mutations of P286R and V411L. The number of positive signals in the cytoplasm was counted, setting the positive threshold and determining the in situ hybridization results. The sensitivity and specificity of BaseScope-ISH assay were compared with that of the Sanger sequencing results. RESULTS: Based on the BaseScope assay, there were 19 positive samples and 32 negative samples in a total of 51 samples. Of the 19 positive samples, 10 samples showed P286R site mutations in the POLE gene, while the other 9 samples were V411L site mutations. Only 1 sample with the V411L site mutation identified by Sanger sequencing showed negative signal value. The remaining 31 cases without the P286R site mutation or V411L site mutations all showed negative signal. This analysis result showed the sensitivity was 95% and the specificity was 100% for the BaseScope assay detecting POLE mutants in high-grade EC. CONCLUSION: In the case of high-grade EC, combined with morphological characteristics, the BaseScope assay can effectively and specifically identify POLE mutation cases, providing a reliable foundation for the application of clinical diagnosis and molecular classification.